PSYCHOLOGY OF INTERNET ADDICTION AND PSYCHO-EMOTIONAL CHARACTERISTICS: https://doi.org/10.5281/zenodo.20658976 - Otamuratov , Rustam; Toshpulatov , Nurmuhammad (Scientific practical conference, 2026)
In this work, theoretical information about the general character traits of individuals prone to Internet addiction and the factors influencing it, as well as facts about the role of emotional intelligence in preventing Internet addiction, are provided.